The characteristics and effects of public participation in Croatian e-consultations in fiscal matters (Public Sector Economics - submission site, 2023)
Public participation in the formulation of fiscal policy is particularly salient, since public finances is a topic relevant for the public in general, although it requires certain level of knowledge about fiscal matters. The purpose of this paper is to investigate the level and the type of public interest in the area of fiscal policy, and to assess the influence of the interested public on the regulation of fiscal policy. In order to do so, authors analyze the implementation of electronic public consultations (e-consultations) in Croatia conducted by the Ministry of Finance in a three-year period. Research findings suggest that even though the level of participation in fiscal policy area does not significantly derogate from the average of e-consultations at the state level, public interest appears to be quite well organized and informed, which positively affects the level of administrative responsiveness in this policy area.